Dynamic Capabilities as the Foundation of Sustainable Competitive Advantage in MSMEs: The Mediating Role of Strategic Innovation - Nuzleha; Khairul Saleh; Reza Pahlepi (Journal of Economics and Management, 2026)
In unstable and technologically advanced marketplaces, Micro, Small, and Medium-Sized Enterprises (MSMEs) are under growing pressure to maintain a competitive edge. Using environmental dynamism as a moderating variable and strategic innovation as a mediating variable, this study investigates the impact of dynamic capacities on sustainable competitive advantage among Indonesian MSMEs. MSMEs in manufacturing and creative services sectors were chosen for high exposure to process adaptation, customer experience changes, product renewal, and competition in digital markets. This study, based on the Dynamic Capabilities View, employed a quantitative explanatory design, drawing on 320 usable responses from top managers and MSME owners in Jabodetabek, Bandung, Surabaya, and Yogyakarta. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used to examine data. The findings demonstrate that strategic innovation (beta = 0.618; p < 0.001) and competitive advantage (beta = 0.342; p < 0.001) are significantly impacted by dynamic capability. Strategic innovation partially mediates the association between dynamic capability and sustainable competitive advantage (indirect effect = 0.279; VAF = 45%) and has a favorable impact on sustainable competitive advantage (beta = 0.451; p < 0.001). Strategic innovation and dynamic capability are positively correlated with environmental dynamism (interaction beta = 0.186; p = 0.002). By elucidating how sensing, seizing, and reconfiguring skills are transformed into sustained competitive advantage through strategic innovation in emerging-market MSMEs, these findings expand the Dynamic Skills View. In practical terms, the results advise MSME owners to develop straightforward market intelligence procedures, expedite innovation-driven decision-making, and reallocate resources through collaborations, digital platforms, and process improvements.